Role of Personal Cultural Orientations in Intercultural Service Encounters - Sharma, Piyush; Wu, Z.; Yong, Su (Emerald Group Publishing, 2016)
Purpose: The purpose of this paper is to address a long-standing gap in current research on intercultural service encounters, by exploring the direct and indirect roles of four personal cultural orientations (PCOs) [independence, interdependence (INT), risk aversion (RSK) and ambiguity intolerance (AMB)]. Design/methodology/approach: A 2 × 2 between-subjects experimental design with customers in two countries (Australia and China) using scenarios to manipulate service outcome (failure or success) and photos of foreigners as customer or employee to prime perceived cultural distance (PCD). Findings: Customers with higher (vs lower) independence perceive greater interaction comfort, service quality and satisfaction (SAT) and are affected to a lesser extent by PCD and service outcome, but those with higher (vs lower) RSK or AMB perceive lower interaction comfort, service quality and SAT and are affected more strongly by PCD and service outcome. Research limitations/implications The authors used an “experimental” design with “imaginary” service scenarios to collect data in “two” countries using “four” PCOs for greater control in this paper, but all of these choices may restrict the generalizability of the findings. Practical implications: Service managers need to look beyond visible cultural differences, such as ethnicity, nationality and language, and focus more on the invisible cultural differences in customs, values and norms, as reflected by the four PCOs in this paper. Originality/value: The authors extend prior research on intercultural service encounters by exploring the moderating effects of PCOs on the influence of service outcome and PCD on interaction comfort, service quality and SAT.